Unilateral versus Bilateral Pedicle Screw Instrumented Transforaminal Interbody Fusion in a Single Level Lumbar Spondylolisthesis - Eldin, Mohamed Mohi; Hassan, Ahmed Salah Aldin; Thabet, Mohamed Alaa Eldin; Refaat, Mohamed I.; Elkady, Ali Y.; Baraka, Mohamed (Open Access Macedonian Journal of Medical Sciences, 2022)
Background The study aims to assess the efficiency, safety and outcome of unilateral pedicle screw fixation with TLIF (Transforaminal lumbar interbody fusion) vs bilateral pedicle screw fixation with TLIF in cases of single level spondylolisthesis by comparing clinical, functional outcome and the complication rates. Methods We prospectively collected demographics and clinical data of the patients with surgically treated single level lumbar spondylolisthesis grade 1 (n=60) with follow up and comparison between clinical/functional outcomes and complication rates between January 2020 and January 2021 at Cairo University hospitals. We allocated the patients with the unilateral pedicle screw fixation with TLIF as group A and the patients with the bilateral pedicle screw fixation with TLIF as group B. Results Clinical outcome showed statistical significance between Group A and Group B (P-value < 0.001); Functional outcome (using Oswestry’s disability index) between group A and B also showed statistical significance (P-value < 0.001) in favor of group B. Complications in group A was higher especially cage migration in 26.7% of cases with p-value of 0.026 while it was only present in 3.3% of the group B cases. Conclusion We concluded that the bilateral approach showed a statistically significant better clinically/functional outcomes with lower rates of complication in comparison with the unilateral approach.